ANALYSIS OF DAILY LANGUAGE USE OF STKIP DARUSSALAM CILACAP STUDENTS IN THE CONTEXT OF INTERPERSONAL COMMUNICATION PSYCHOLINGUISTIC STUDY - Renovriska, Melia Dwi; Darmawan, Almas Rifqi (Journal of Language, Literature and Teaching, 2025)
This study aims to analyze the use of everyday language in the context of interpersonal communication using a psycholinguistic approach in an academic setting. Through in-depth interviews, document analysis, and psycholinguistic studies, findings reveal variations in language style depending on the communication context. Students tend to adapt their language according to the situation, both inside and outside the classroom. Text message analysis also reveals the impact of social media on language use. The positive correlation between positive language expressions and positive emotions suggests that language can reflect and influence the emotional atmosphere in interpersonal communication. Practical implications include the development of communication training programs tailored to specific contexts, while recommendations for further research involve further exploration of the influence of social media and cross-cultural research on changes in everyday language.Keywords: Language, Communication, Interpersonal Communication, Psycholinguistic Studies.